2014
DOI: 10.1017/neu.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviour and lipid levels in unipolar and bipolar depression

Abstract: The results of our study support a majority of research showing the association in depressed patients between suicidal behaviour and low levels of total and LDL cholesterol. In addition, the data suggest a similar association with low total lipids, and in some instances, with low triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…This corroborates the results of a previous Polish study performed by Rabe-Jablonska and Poprawska [9] in patients with acute depressive episodes, in which lower levels of total and LDL cholesterol were observed in those with suicidal behavior. Also, in one of our own previous investigations, a significant association was found between low total cholesterol, LDL cholesterol, and total lipids and suicidal thoughts, tendencies, and attempts in both male and female patients with unipolar and bipolar depression [10]. On the other hand, no association with HDL cholesterol was observed in these patients for any suicidal parameter, which was also the case in the present study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This corroborates the results of a previous Polish study performed by Rabe-Jablonska and Poprawska [9] in patients with acute depressive episodes, in which lower levels of total and LDL cholesterol were observed in those with suicidal behavior. Also, in one of our own previous investigations, a significant association was found between low total cholesterol, LDL cholesterol, and total lipids and suicidal thoughts, tendencies, and attempts in both male and female patients with unipolar and bipolar depression [10]. On the other hand, no association with HDL cholesterol was observed in these patients for any suicidal parameter, which was also the case in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Many subsequent meta-analyses performed in patients with depression demonstrated that, in most studies (including various study designs) a relationship between low serum cholesterol and suicide has been suggested [68]. Such a relationship was also observed in a Polish population of depressed patients [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…During their follow-up, the TC levels remained low ( 18 ). Moreover, in depression patients suffering from suicidal behavior, LDL-c, TC levels ( 26 ) and triglycerides (TG) levels ( 27 , 28 ) were significantly lower. However, it has been reported that patients with depression who attempt suicide have higher HDL-c levels ( 27 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some authors revealed a positive association between serum lipid levels and suicide attempt (Brunner et al,2006;Baek et al, 2014). Finally, cross-sectional (Ainiyet et al,2014;Loas et al, 2016) and cohort studies (Fiedorowicz and Coryell, 2007) including depressive subjects among MDD, bipolar and schizoaffective disorder showed different results. Similarly studies including individuals with bipolar (d'Ambrosio et al,2012;Shakeri et al,2014;Ahmadpanah et al,2015), schizoaffective (Marcinko et al,2008) or mixed mood disorders (Kunugi et al,1997;Guillem et al, 2002;da Graca Cantarelli et al,2015) produced controversial results.…”
Section: Observational Studiesmentioning
confidence: 97%